Pengaruh Penggunaan Media Multifunction Board Terhadap Kemampuan Mengenal Lambang Bilangan Anak Usia 4-5 Tahun di PAUD Percontohan Plamboyan 3 Karawang Barat - Fatharani, Firda Amalia; Syafrida, Rina; Riana, Nancy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine how much influence the use of multifunction board media has on the ability to recognize the number symbols of children aged 4-5 years at PAUD Percontohan Plamboyan 3 Karawang Barat. This study used a pre-experimental design with a one group pretest-posttest design. The population in the study were 54 students. Data collection tools used in this study were notes, number symbol recognition ability assessment instruments for pretest-posttest. Based on the results obtained from before being given treatment, the average value of children is 32.0 with the criteria starting to develop. While after using multifunction board media there is an increase from the average value of 32.0 to 51.7. By using the paired sample t test calculation that the tcount value is obtained 6.440 and the ttable is obtained 1.833 which means that the tcount value> ttable. So it can be concluded that there is a positive and significant influence in the use of multifunction board media on the ability to recognize number symbols of children aged 4-5 years.